Seasonal variability of eddy kinetic energy in the north Indian Ocean - Sun, Chunjian; Zhang, Anmin; Jin, Baogang; Wang, Xidong; Zhang, Xiaoshuang; Zhang, Lianxin (Frontiers in Marine Science, 2022)
The seasonality of eddy kinetic energy (EKE) is analyzed in the north Indian Ocean by adopting high-resolution ocean reanalysis data. Significant eddy energy can be mainly spotted in six regions, including the Somali Current (SC) region, the Gulf of Aden, the Laccadive Sea, the east of Sri Lanka, the East Indian Coastal Current (EICC) region, and the northwest of Sumatra. As the most energetic region, the EKE averaged above 200 m could exceed 0.15 m2·s-2 in the SC region, whereas the mean EKE above 200 m is less than 0.04 m2·s-2 in the other regions. The barotropic and baroclinic instabilities are vital to eddy energy, and the contribution of each term in the barotropic/baroclinic equations varies with season and region. In the SC region and EICC region, EKE is primarily generated by barotropic conversion due to the sharp velocity shear caused by the strong SC during the summer monsoon and the EICC from March to June. For the other regions, the leading source of EKE is the eddy potential energy (EPE), which is extracted from available potential energy of mean flow via baroclinic conversion, and then the EPE is converted into EKE through vertical density flux. Once generated, EKE will be redistributed by pressure work and advection via eddy energy flux, which varies in sync with the monthly variation of total EKE, transporting EKE to the adjacent region or deeper layer. From the vertical aspect, eddy energy conversions are more prominent above 200 m. The maximal EKE and barotropic conversion mostly occur at the surface, whereas the EPE and baroclinic conversion may have two peaks, which lie at the surface and in the thermocline. Using the satellite altimeter data and wind data, we further investigate the impact of geostrophic eddy wind work, which reveals a slightly dampening effect to EKE in the north Indian Ocean.